Complications of Cranioplasty. Issue 5 (July 2018) - Sahoo, Nanda Kishore; Tomar, Kapil; Thakral, Ankur; Rangan, N. Mohan
Abstract : Abstract: Cranioplasty is a time-honoured surgical procedure to restore the calvarial form and function that is associated with a relatively high complication rate. The present article analyzed various complications and reviewed the complications based on study of the relevant research in the craniofacial literature. Complications were broadly divided into 2 groups, intraoperative and postoperative, for ease of understanding. The etiological factors, local and systemic condition of the patient, prevention, and management of various complications were widely discussed. The article also highlighted problems and complications associated with various reconstructive materials. Insights into various complications of cranioplasty enable surgeon to understand them better, minimize the chances of occurrence, and improve surgical outcome. In spite of reported high rate of complications, serious complications like meningitis, air embolism, and death are rare.